After Fukushima: The precautionary principle revisited - Huber, Wolfgang (Verbum et ecclesia, 2012)
Etienne de Villiers, more than other theologians, elaborates on basic elements of a Christian ethics of responsibility. He distinguishes between retrospective and prospective responsibility. The prospective aspect attracted awareness after the nuclear accident in the Fukushima reactors on 11 March 2011. The question on how to respond in an ethically responsible manner to catastrophic risks was put back on the agenda. The article takes up this question and discusses the answer given in the international debate by the introduction of the ‘precautionary principle’. The principle is described with its background in the ‘heuristics of fear’, proposed by the philosopher Hans Jonas. Four criticisms are discussed in detail relating to the problems of scientific uncertainty, the burden of proof, the weight of damages and the perils of precaution. That leads to a reformulation of the precautionary principle as a concrete element within an ethics of responsibility.